2021
DOI: 10.1016/j.lanwpc.2021.100225
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Lifestyle Risk Behaviors among Vietnamese Adolescents and Roles of School: A Bayesian Multilevel Analysis of Global School-Based Student Health Survey 2019

Abstract: Background Adolescence is a vulnerable period for many lifestyle risk behaviors. In this study, we aimed to 1) examine a clustering pattern of lifestyle risk behaviors; 2) investigate roles of the school health promotion programs on this pattern among adolescents in Vietnam. Methods We analyzed data of 7,541 adolescents aged 13–17 years from the 2019 nationally representative Global School-based Student Health Survey, conducted in 20 provinces and cities in Vietnam. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 51 publications
2
21
1
Order By: Relevance
“…In our study, we found that insufficient fruits, insufficient vegetables and fats food consumption are the three common risk factors among the adolescent. This is similar to an analysis in Vietnam that reported low fruit/vegetable intake and unhealthy diet were common among school-going adolescents aged 13–17 years [ 7 , 9 ]. Similar to some other Asian countries, we found that smoking and alcohol prevalence is comparatively low in Bangladesh [ 8 , 10 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our study, we found that insufficient fruits, insufficient vegetables and fats food consumption are the three common risk factors among the adolescent. This is similar to an analysis in Vietnam that reported low fruit/vegetable intake and unhealthy diet were common among school-going adolescents aged 13–17 years [ 7 , 9 ]. Similar to some other Asian countries, we found that smoking and alcohol prevalence is comparatively low in Bangladesh [ 8 , 10 ].…”
Section: Discussionsupporting
confidence: 89%
“…Similar to some other Asian countries, we found that smoking and alcohol prevalence is comparatively low in Bangladesh [ 8 , 10 ]. Although in our study we did not explore any school health promotion programs for improving adolescent health wellbeing, a recent study in Vietnam reported high quality of health promotion programs associated with lower the odds of lifestyle risk behaviors [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 , 2 Risk factors such as poor diet, smoking, sedentary behaviour, and overweight/obesity increase the risk of NCDs, with most of these commencing in early life, impacting health throughout the life course. 3 Among adolescents aged 10–20 years, physical inactivity and sedentary behaviour (e.g., watching television, gaming, and computer and smartphone use) have been linked with increased obesity and adiposity, poor diet (insufficient fruits and vegetable consumption, salt, sugar-sweetened beverages and saturated fat consumption, low iron etc), depression, and reduced quality of life. 4 , 5 Globally, unhealthy diet mainly from the consumption of sugar-sweetened beverages and saturated fat increases the risk of CVD.…”
Section: Introductionmentioning
confidence: 99%